The reliability of a commonly used (CatapultTM Vector S7) microtechnology unit to detect movement characteristics used in court-based sports - Mackay, L.; Sawczuk, T.; Jones, B.; Darrall-Jones, J.; Clark, A.; Whitehead, S. (Journal of Sports Sciences, 2025)
This two-part study evaluated the inter- and intra-unit reliability of Catapult Vector S7 microtechnology units in an indoor court-sport setting. In part-one, 27 female netball players completed a controlled movement series on two separate occasions to assess the inter- and intra-unit reliability of inertial movement analysis (IMA) variables (acceleration, deceleration, changes of direction and jumps). In part-two, 13 female netball players participated in 10 netball training sessions to assess the inter-unit reliability of IMA and PlayerLoadTM variables. Participants wore two microtechnology units placed side-by-side. Reliability was assessed using intraclass correlation coefficient (ICC), coefficient of variation (CV) and typical error (TE). Total IMA events showed good inter-unit reliability during the movement series (ICC, 1.00; CV, 3.7%) and training sessions (ICC, 0.99; CV, 4.5%). Inter-unit (ICC, 0.97; CV, 4.7%) and intra-unit (ICC, 0.97; CV, 4.3%) reliability for total IMA jump count was good in the movement series, with moderate CV (7.7%) during training. Reliability decreased when IMA counts were categorised by intensity and movement type. PlayerLoadTM (ICC, 1.00; CV, 1.5%) and associated variables revealed good inter-reliability, except peak PlayerLoadTM (moderate) and PlayerLoadSLOW (moderate). Counts of IMA variables, when considered as total and low-medium counts, and PlayerLoad variables are reliable for monitoring indoor court-sports players.